Persuasive Multimedia Design Model for Game-Based Learning to Enhance Children's Awareness of Child Sexual Abuse - Othman, Azliza; Shaari, Nassiriah; Abdul Salam, Sobihatun Nur; Kanagasabai, Suras (UUM, 2022)
With the high prevalence of Child Sexual Abuse (CSA) cases and the negative effects associated with CSA abusive experience, research attention must turn toward educating children about safety from sexual abuse. Therefore, it is essential to provide knowledge about safety to children using appropriate learning programs to be aware of and understand the danger of CSA. They can take necessary actions when CSA cases occur around them. Today, learning can be supported by persuasive technology and game-based learning (GBL) to ensure that learning and understanding the concept are more effortless and effective. Therefore, this research aims to formulate a persuasive game-based learning model for children's safety from CSA. The specific objectives of this research are to 1. identify appropriate components involved in game-based learning and persuasive multimedia applications, 2. construct a persuasive game-based learning model to enhance children's awareness of CSA, and 3. validate the proposed model. Three methodology phases have been conducted: theoretical, suggestion and model construction, and model validation. Expert review sessions were conducted with five experts. The majority of the experts are satisfied with the proposed model. Based on the suggestion and feedback from experts, the model has been revised for better impression and to enhance the readability of the model for reference and guidance to educational, edutainment, and game developer.